Maternal body composition and birth weight. (19th February 2014) - Connor, Clare O'; O' Higgins, Amy; Segurado, Ricardo; Turner, Michael J.; Stuart, Bernard; Kennelly, Máireád M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Birth weight (BW) prediction is an important part of obstetric management. It is a key determinant of perinatal outcome with poor outcomes resulting from delivering macrosomic neonates or growth‐restricted neonates. Maternal obesity, assessed by BMI, has been associated with an increased risk of fetal macrosomia, neonatal adiposity and metabolic syndrome. There is a paucity of data in the literature on maternal body composition and its relationship to BW. What does this study add? First trimester maternal body composition was assessed accurately and objectively by bioelectrical impedance analysis and correlated to BW. We accurately identify which maternal body composition parameters including visceral fat and waist circumference independently influence BW. We also explore customised centiles and population based centiles at birth. Potentially, this study may help to identify a modifiable risk factor to reduce the incidence of macrosomia and neonatal adiposity.